GLOBAL PREVALENCE OF CHLAMYDIA INFECTION AMONG WILD BIRDS AS PUBLIC HEALTH CONCERNS: A SYSTEMATIC REVIEW AND META-ANALYSIS - T. I. Mamun; J. Rahman; M. J. Hossain; R. Hasan; M. T. Neoaj; M. M. Mia (Bulgarian Journal of Veterinary Medicine)
Chlamydia has a significant worldwide zoonotic impact and can infect a variety of animal species, including wild birds and humans. Birds are frequently susceptible to the Chlamydia pathogen, which can lead to avian chlamydiosis and the human disease ornithosis. The present study investigated wild birds Chlamydia prevalence using a systematic review and meta-analysis. Scientific papers from Sco-pus, PubMed, Google Scholar, and local journals were evaluated between November 1 and December 10, 2022. The investigators conducted a meta-analysis of 29 studies, which included 48 trials to as-sess the prevalence of Chlamydia. The pooled prevalence of the infection was 22% (95% CI: 15–28%) based on the findings of the meta-analysis. Following that, a survey of the continents was con-ducted, with Europe having the highest prevalence rate (26%), followed by Australia (22%), South America (22%), Asia (15%), and North America (13%). Italy had the highest prevalence rate, and Sweden had the lowest prevalence rate among European countries. Egypt had the highest prevalence rate of 75%, as shown in a single study. The prevalence rate for Chlamydia species was 21% (CI: 1328%), with Chlamydia psittaci being the most common. This finding provides more evidence that wild birds are a potential reservoir for the spread of the Chlamydia disease, since they are known to be carriers of the infection. In order to acquire a more precise estimate of worldwide prevalence, fur-ther molecular studies are recommended.